‘Doing’ leadership in interaction : a discursive investigation of emerging leadership construction in small group interaction - Dong, Shujing (2016)
Exerting influence is essential in social life but how to exert influence over and lead others is a complex but intriguing question. Although the dynamic and procedural nature of leadership construction has drawn increasing attention in recent years, investigations on how interactional practices may be employed in order to emerge as a leader in non-hierarchal settings remain lacking. The present research aims to explore how emerging leadership is constructed through interactions in the Chinese context. In particular, this study emphasizes three aspects: interactional processes of micro-level emerging leadership construction, interactional strategies to construct emerging leadership, and interactional predictors of leadership emergence. The study adopts the combined methods of leaderless group discussion and follow-up interviews to collect data on actual leadership emergence practices and participants’ perceptions of emerging leadership construction. Conversation analysis was applied to reveal the processes and strategies by which emerging leadership is constructed. To identify predictors of leadership emergence, statistical analysis of data on participants’ interactional strategies and perceived leadership was conducted. It was found that emerging leadership is collaboratively constructed by participants claiming, negotiating and granting leadership positions in agenda-related proposal sequences and decision-making sequences. Six possible responses to negotiate leadership claims were also identified. Interactional strategies in terms of turn-taking, linguistic formats, prosodic cues and nonverbal behaviors were found to facilitate the construction of emerging leadership in two manners, namely, domineering and facilitative. Participants’ reports in follow-up interviews also aligned with the findings about leadership processes and leadership strategies found in the interactional data. In addition, the results of correlation analysis and mediation tests suggested that both how much participants say and what they say predict leadership emergence, but what participants say is the root cause of how much they say being predictive of leadership emergence. The present study has both theoretical and practical implications, as it advances the understanding of interactional patterns, strategies, and predictors of leadership emergence, and it offers interactional guideline for leadership training and practices.